The Impact of Influencers on Consumer’s Content Consumption of Online Streaming Platforms in Delhi - Bharat, Kumar; Srivastava, Sudesh; Singh, Shivanshi; Chaddha, Kriti (International Journal of Engineering and Management Research, 2024)
This study aims to provide fruitful insights regarding the impact of influencers on digital content consumption on online streaming platforms among consumers of Delhi by considering some demographic aspects. We did a systematic literature review to find out the impact of influencers on digital content consumption in Delhi. It also consists of the various genres and streaming platforms that are famous nowadays in Delhi. The Systematic literature review technique is used in a way that will find the appropriate variables and entertain the exact research gap found during the process. This study includes 250 individuals from different characteristics with the help of convenient sampling techniques. It also indicates the perception of people residing in Delhi regarding content consumption across different online streaming Platforms. The outcome of this study suggests the role of influencers affecting various demographics and consumer engagements while consuming digital content.